Taqalid Insyad Syi‘ri Li Khomsatun Limu‘alajati Tafassy al-Waba’ COVID-19 (Dirasah Finomonologiyah Lifahmi at-Taqalid ad-Diniyyah bi Malang Indonesia) - Wildana Wargadinata; Iffat Maimunah; Aunur Rofiq; Gareeb Allah Babiker Mustafa (el Harakah: Jurnal Budaya Islam, 2022)
يهدف هذا البحث إلى فهم دقيق لكيفية حياة سكان مدينة مالانج وتفسير تقاليد إنشاد شعر «لي خمسة» كممارسة للتعاليم الدينية القادرة على درء تفشي كوفيد-19. يستند هذا البحث إلى منهج البحث الفينومنولوجي، ووجد هذا البحث أن إنشاد شعر «لي خمسة» هو الممارسة للدعاء وطلب الشفاعة والتوسل. فالتوسل هو التقرب إلى الله تعالى بطاعته وعبادته واتباع أنبيائه ورسله وكل عمل يحبه الله ويرضاه، وهي السلاح النهائي في التعامل مع تفشي فيروس كوفيد-19. هذا التقليد هو وضع سياق للتعاليم الدينية القادرة على تقوية الإيمان في مواجهة تفشي كوفيد-19، كإحياء الإسلام والشفاء الذاتي. تماشياً مع ذلك، اقترح هذا البحث طريقة للتعامل مع حالات تفشي المرض ليس فقط من خلال التأكيد على البروتوكولات الصحية والإجراءات الطبية ولكن أيضًا الانتباه إلى أهمية ثقافة الممارسات الدينية المجتمعية، والتي لا تعمل فقط على رعاية الممارسات الدينية، ولكن أيضا الحفظ على الحكمة المحلية. This study aims to understand in depth how the people of the city of Malang live and interpret the tradition of reading Li Khomsatun’s poetry as a practice of religious teachings that can ward off the COVID-19 outbreak. This study is based on a phenomenological study approach and finds that reading Li Khomsatun’s poetry is a practice of prayer, intercession, and tawassul, which is the ultimate weapon in dealing with the COVID-19 outbreak. This tradition contextualizes religious teachings that can strengthen faith in the face of the COVID-19 outbreak as self-healing and living Islam. In line with that, this study suggests a method of handling outbreaks by emphasizing health protocols and medical procedures and paying attention to the importance of the culture and culture of community religious practices, which not only function to care for religious practices but also maintain local wisdom.